The High Vocational Innovation Scholarship Program: A TVET Curriculum Continuous Quality Improvement Using Feedback from Stakeholders - Papanai, Rinradee; Poolkrajang, Akkarat (Journal of Technical Education and Training, 2023)
This research aimed to 1) evaluate the TVET curriculum of Vocational Education Institutions participating in the high vocational innovation scholarship program, the Equitable Education Fund (EEF), Thailand by applying the CIPPIEST Model and 2) analyse the feedback from this evaluation process. Key informants from 60 vocational education institutions in all regions of Thailand and participate in the high vocational innovation scholarship program for Batch 1 (Academic Year 2019) and Batch 2 (Academic Year 2020) under the EEF. Each institution consists of 1 college administrator and 1 teacher or instructor who perform academic duties and implement the TVET curriculum in the institution, totalling 120 persons. Instrumentation involved a curriculum evaluation form containing items based on the CIPPIEST Model and administered online with google forms to facilitate the sample’s responses. Data analysis included frequency, percentage, mean, standard deviation, and content analysis. Results of the evaluation with the CIPPIEST Model showed the overall mean at a high level. The 3 top-ranked issues rated at a high level were sustainability evaluation; product evaluation; and effectiveness evaluation, respectively. The 4 lower-ranked issues also rated at a high level were transportability evaluation; process evaluation; context evaluation and input evaluation, respectively. Additionally, it was found that educational institutions with leadership-oriented administrators are able to lead better and inspire their personnel to work together successfully; drive for co-development of educational curriculum that fits the needs, proficiency, social and cultural contexts of the local community where the institution is located; and also establish collaboration among personnel and external agencies to participate in the management of education effectively, thus bringing about an innovative and unique curriculum at a particular educational institution.